Analisis Kontribusi Pendidikan Agama Islam dalam Membentuk Karakter Toleransi Remaja di Era Globalisasi - Jaya, Hendri; Rudiansyah, Firman (An Naba, 2025)
This study aims to explain how Islamic Religious Education (PAI) can help shape a tolerant character among adolescents, especially in today's era of globalization. The research background arises from the phenomenon of increasing intolerant behavior among adolescents, both in schools and on social media. This demands a strategic role for PAI in instilling the values of religious moderation, mutual respect, and acceptance of differences. In this study, we used a descriptive qualitative approach and analyzed the content of PAI curriculum documents, teaching materials, and relevant learning activities. Data were collected through literature studies, such as textbooks, scientific journals, and education policies, as well as observations of learning practices that integrate the value of tolerance. The analysis results indicate that PAI makes a significant contribution to shaping a tolerant character in adolescents. This is evident in the internalization of the values of tasamuh (compassion), ta'awun (compassion), and ukhuwwah (brotherhood), both explicitly through the subject matter and implicitly through teacher role models and cross-cultural extracurricular activities. This contribution is particularly important in the era of globalization, which is characterized by information transparency, cross-cultural interaction, and the potential for value friction. Therefore, this study recommends that Islamic Religious Education (PAI) learning continue to be developed with a contextual, participatory, and collaborative approach to strengthen tolerance among adolescents.